Geographic and Temporal Trends in Fake News Consumption During the 2016 US Presidential Election - Fourney, Adam; Racz, Miklos Z.; Ranade, Gireeja; Mobius, Markus; Horvitz, Eric (Proceedings of the 2017 ACM on Conference on Information and Knowledge Management, 2017)
We present an analysis of traffic to websites known for publishing fake news in the months preceding the 2016 US presidential election. The study is based on the combined instrumentation data from two popular desktop web browsers: Internet Explorer 11 and Edge. We find that social media was the primary outlet for the circulation of fake news stories and that aggregate voting patterns were strongly correlated with the average daily fraction of users visiting websites serving fake news. This correlation was observed both at the state level and at the county level, and remained stable throughout the main election season. We propose a simple model based on homophily in social networks to explain the linear association. Finally, we highlight examples of different types of fake news stories: while certain stories continue to circulate in the population, others are short-lived and die out in a few days.